Managing packaging design for sustainable development : a compass for strategic directions - Hellström, Daniel; Olsson, Annika, 1962- (John Wiley & Sons, 2017)
Packaging design is a powerful vehicle for making our lives friendlier, our planet greener and our businesses richer. It is an essential link between the producer and the customer, where it contributes to the positioning and presentation of a product; and on many occasions, the use of the product after purchase. What is missing is a compass that can guide practitioners in the right direction. This is particularly so in the field of packaging where the routes you take may contradict rather than contribute to sustainable development. Managing Packaging Design for Sustainable Development: A Compass for Strategic Directions emphasizes the need to rethink packaging system design, by presenting a strategic packaging design tool; a compass. The compass encourages you to go off-road, to develop and innovate, and to remake the packaging design solution that previously was best practice. Theory and practical applications are balanced by outlining the most crucial tenets of packaging design for sustainability and by illustrating wide range of real-life cases that will inspire and challenge the mindsets of those who apply the compass in packaging design related projects. This is a must-have book for designers, engineers, logisticians, marketers, supply chain professionals and other managers who seek guidance on sustainable solutions through packaging design.
Keywords: Packaging -- Design -- Environmental aspects.; Package goods industry.; Sustainable engineering.; elektronické knihy; electronic books